Pengembangan Modul Praktikum Anatomi Fisiologi Manusia Tingkat Perguruan Tinggi - Ismi Nurul Qomariyah; Diyah Ayu Widyaningrum (IKIP Budi Utomo Malang, 2022)
Human physological anatomy is one of the courses that must be taken at the S1 level of Biology Education. This lecture is carried out in 2 activities, namely theoretical lecture activities and lectures in practicum activities. Theoretical lecture activities contain lecture activities in the context of mastering the material of the skeletal system, muscular system, circulatory system, digestive system, endocrine system, nervous system, respiratory system and human immune system. Practicum activities are carried out in the laboratory with the aim of students mastering work procedures safely in the Biology Laboratory. Researchers make observations during this lecture activity and there is a main problem that must be resolved immediately, namely the absence of a practicum module for the Human Physiology Anatomy course. This results in students having difficulty in proving concepts and theories that they have obtained from theoretical lecture knowledge. In addition, it also makes it difficult for students to do practicum work in the laboratory. Therefore, it is necessary to take steps to solve these problems by developing practicum modules that will provide instructions in carrying out practicum. The development chosen by the researcher in this case uses a 4D model that contains define, design, develop, and disseminate. The instruments used in this test include: (1) Questionnaire of validation sheets of human physiological anatomy material experts, (2) questionnaires of validation sheets from experts in learning media, (3) response questionnaires of students who take human physiology anatomy classes, and (4) response questionnaires of lecturers in human physiology anatomy classes. Based on the results of the development of the human physiology anatomy practicum module that has been developed, it can be said that it has been in accordance with the development objectives. This can be observed based on the series of development activities that have been completed by researchers until obtaining the product of the human physiology anatomy practicum module.